Bi (at) S doped g-C3N4 nano material as well as preparation method and application thereof

By preparing Bi@S doped g-C3N4 nanomaterials and adjusting electron transport, the problem of insufficient sensitivity and accuracy of existing electrochemical detection methods when detecting heavy metal ions in water is solved, and high sensitivity specificity detection is achieved, reducing costs and improving efficiency.

CN119637818APending Publication Date: 2025-03-18Hefei Comprehensive Science Center Environmental Research Institute
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762085.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing electrochemical detection methods lack sensitivity and accuracy when detecting heavy metal ions in water, and lack effective non-metallic element adjustment methods to improve detection performance.

Method used

By preparing Bi@S doped g-C3N4 nanomaterials, g-C3N4 is doped using Bi and S elements to regulate electron transport at metal active sites, thereby improving the sensitivity and accuracy of electrochemical detection.

Benefits of technology

Highly sensitive specific detection of specific heavy metal ions is achieved, which reduces experimental costs and improves experimental efficiency, and the detection limit reaches 0.04μM, which is lower than the national standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637818A_ABST
    Figure CN119637818A_ABST
Patent Text Reader

Abstract

The invention discloses a Bi (at) S doped g-C3N4 nano material and a preparation method and application thereof, and the preparation method comprises the following steps: calcining urea to obtain a g-C3N4 substrate material; the preparation method comprises the following steps: adding the graphene oxide, Bi (NO3) 3.5 H2O and a sulfur-containing non-metallic material into deionized water, and heating and stirring to obtain a uniform mixed solution; heating and evaporating the mixed solution to dryness to obtain a precursor; uniformly grinding the mixture; and calcining the ground precursor, cooling and then grinding to obtain the Bi (at) S doped g-C3N4 nano material. According to the invention, the Bi element is electronically adjusted by S through doping and calcining, so that more electrons flow to heavy metal lead ions in the electrochemical detection process, thereby improving the detection sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of water quality detection, in particular to the field of electrochemical detection of heavy metals, and specifically to a preparation method of a Bi@S-doped g-C3N4 sensitive material and its application in electrochemical detection. Background Art

[0002] Lead ion (Pb 2+ ) is a toxic heavy metal widely present in the environment, which has serious harm to the environment and human health. 2+ It can enter the ecosystem through air, water, soil, etc., causing poisoning to plants, animals and microorganisms. Plants absorb Pb 2+ After that, it will affect its growth and metabolism, reduce yield and quality; animals ingest Pb 2+ After being added, it will accumulate in the body, affecting the nervous system, digestive system and reproductive system, and even causing death. 2+ Therefore, it is necessary to strengthen the monitoring and control of lead pollution, control and reduce Pb in the environment. 2+ The content of is of great significance for protecting the ecosystem and human health.

[0003] Electrochemical sensing technology has been widely used in many fields due to its advantages such as simple equipment, sensitive detection, easy integration and field application, and has become one of the important means of modern analytical chemistry and sensor technology. With the continuous advancement of technology, electrochemical sensors will play an important role in more fields, providing strong technical support for environmental protection, food safety, biomedicine and industrial process control. At present, electrochemical detection methods have been widely used in the detection of heavy gold ions in actual water bodies.

[0004] In recent years, there have been more and more studies on nanomaterial-modified electrodes based on g-C3N4 for electrochemical trace detection of heavy metal ions in water. However, there have been no reports on the use of non-metallic elements to regulate the electron transport of metal active sites, thereby enhancing the sensitivity and accuracy in the detection process. Therefore, the construction of Bi@S co-modified electrodes based on g-C3N4 substrates has high practicality and reliability for the electrochemical specific detection of Pb(II). Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a Bi@S-doped g-C3N4 nanomaterial, which can achieve highly sensitive and specific detection of specific heavy metal ions, thereby reducing experimental costs and improving experimental efficiency.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing Bi@S-doped g-C3N4 nanomaterials comprises the following steps:

[0008] S1, calcining urea to obtain a g-C3N4 substrate material;

[0009] S2, adding g-C3N4 substrate material, Bi(NO3)3·5H2O and sulfur-containing non-metallic material into deionized water, heating and stirring to obtain a uniform mixed solution;

[0010] The sulfur-containing non-metallic material is thioacetamide or L-cysteine;

[0011] S3, heating and evaporating the mixed liquid to obtain a precursor; and then grinding it uniformly;

[0012] S4. The ground precursor is calcined, cooled, and then ground again to obtain Bi@S-doped g-C3N4 nanomaterials.

[0013] In a further embodiment, the calcination conditions in steps S1 and S4 are the same, both of which are heated in two stages in a muffle furnace, wherein the first stage is to heat the temperature to 350-450°C and keep it for 1-2 hours; the second stage is to continue heating to 500-600°C and keep it for 1-2 hours, and then anneal. The heating rate of these two stages is 5°C / min.

[0014] In a further embodiment, in step S2, the mass ratio of the g-C3N4 base material and Bi(NO3)3·5H2O in the mixed solution is 16:(5-20), and the molar ratio of Bi and S elements is (1-4):133.

[0015] In a further embodiment, the heating and stirring in step S2 is performed at 40-70° C. using magnetic stirring for 1-3 hours.

[0016] In a further embodiment, the heating and drying of the mixed solution in step S3 is performed by using a rotary evaporator at 30-60° C. and 0.1-0.9 kp, mainly to evaporate the deionized water in the mixed solution.

[0017] The second object of the present invention is to provide Bi@S doped g-C3N4 nanomaterials prepared by the above preparation method.

[0018] The third invention objective of the present invention is to provide the application of the above-mentioned Bi@S doped g-C3N4 nanomaterial in detecting heavy metal ions in water.

[0019] In a further embodiment, the heavy metal ion is Pb(II), and its detection limit (LOD) is 0.04 μM and the detection sensitivity is 57.45 μA / μM.

[0020] In a further solution, the detection of heavy metal ions in water is carried out using a three-electrode detection system, wherein the three-electrode detection system includes a working electrode, and the working electrode is a GCE electrode with a surface coated with Bi@S doped g-C3N4 nanomaterial.

[0021] The detection conditions of the three-electrode detection system are: pH=5, HAc-NaAc buffer solution, enrichment time of 180s, and enrichment voltage of -1.1V.

[0022] The detection limit (LOD) of the Bi@S doped g-C3N4 nanomaterial working motor for Pb(II) is 0.04 μM, which is significantly lower than 0.048 μM specified in the national "Sanitary Standard for Drinking Water" (GB5749-2022).

[0023] The mixture of the present invention is ground separately before and after calcination, the purpose of which is to ensure that the product can remain uniform and Bi and S can be evenly distributed in g-C3N4.

[0024] The present invention dopes g-C3N4 with Bi and S. Due to the N vacancies in the g-C3N4 base material, the S element performs electronic regulation on the Bi element through doping and calcination, so that in the electrochemical detection process, more electrons flow to the heavy metal lead ions, thereby improving the detection sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of the material of the present invention;

[0026] Figure 2 is the SWASV response curve of Bi@Sg-C3N4 nanomaterials to Pb(II);

[0027] Figure 3 The detection response of different added amounts of Bi(NO3)3·5H2O to 0.6μM Pb(Ⅱ). DETAILED DESCRIPTION

[0028] The bismuth nitrate pentahydrate [Bi(NO3)3·5H2O], urea [CO(NH2)2], thioacetamide [C2H5NS], and L-cysteine ​​used in the following examples were purchased from Sinopharm Chemical Reagent Co., Ltd. All chemical reagents involved were of analytical grade and used directly without other purification or purification treatment.

[0029] Embodiment 1:

[0030] S1. Place urea in a muffle furnace and set the temperature program to two stages: the first stage is to heat up to 400°C at a heating rate of 5°C / min and keep it for 1 hour; the second stage is to heat up to 500°C at a heating rate of 5°C / min and keep it for 2 hours, then anneal to obtain a g-C3N4 substrate material.

[0031] S2. Add 16 mg of the g-C3N4 substrate material prepared above, 15 mg of Bi(NO3)3·5H2O, and 100 mg of thioacetamide to 20 mL of deionized water (the molar ratio of Bi to S is 3:133), and stir magnetically at 50°C for 2 hours to obtain a uniform mixed solution.

[0032] S3, evaporating the mixed solution to dryness at 50° C. and 0.9 kp using a rotary evaporator to obtain a powdered solid, and grinding the powdered solid to obtain a ground material;

[0033] S4. Place the ground material in a muffle furnace and perform two-stage calcination as in step S1, then cool to room temperature, grind, and sieve to obtain Bi@S-doped g-C3N4 nanomaterials.

[0034] like Figure 1 This is a scanning electron microscope image of the Bi@S doped g-C3N4 nanomaterial prepared in Example 1. It can be seen from the image that the basic morphology of the material is lamellar, which provides a good place for adsorbing more heavy metal ions.

[0035] Test example 1:

[0036] The electrochemical experiment was conducted on the Bi@S doped g-C3N4 nanomaterial prepared in Example 1, as follows:

[0037] 1) Test system

[0038] All electrochemical experiments were performed on a CHI 760E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd., China.

[0039] A three-electrode system was used in this experiment, in which the working electrode was Bi@S-doped g-C3N4 / GCE, the reference electrode was Ag / AgCl (3 mol / L KCl), and the counter electrode was a platinum wire electrode.

[0040] The working electrode Bi@S doped g-C3N4 / GCE is prepared by adding the Bi@S doped g-C3N4 nanomaterial prepared in Example 1 into water and stirring to obtain a 0.1 mg / mL Bi@S doped g-C3N4 nanomaterial suspension, and 4 μL of the suspension is drop-coated on the surface of the treated GCE electrode and dried at room temperature to obtain the working electrode Bi@S doped g-C3N4 / GCE.

[0041] The treatment of the GCE electrode is as follows: a bare glassy carbon electrode (GCE) with a diameter of 3 mm is selected, and it is first polished with 0.1 μm and 0.05 μm alumina powder respectively; then the reversibility of the glassy carbon electrode is tested in a mixed solution of 0.005 mol / L K3[Fe(CN)6] and 0.1 mol / L KCl. When the potential difference between the oxidation peak and the reduction peak is less than 0.084 V, it means that the electrode has good reversibility; finally, the polishing powder on the exposed GCE surface is removed by ultrasonic treatment for 90 seconds in nitric acid aqueous solution (the volume ratio of nitric acid to water is 1:1), ethanol and deionized water solution, and then the water droplets on the electrode surface are blown away with nitrogen; the treated GCE electrode is obtained.

[0042] 2) Preparation of test samples

[0043] HAc-NaAc buffer solutions with different pH values ​​were prepared using 0.1 mol / L acetic acid and sodium acetate stock solutions, and an alkaline buffer solution was obtained by adding 0.1 mol / L sodium hydroxide solution.

[0044] PBS buffer solutions with different pH values ​​were prepared using 0.1 mol / L disodium hydrogen phosphate and potassium dihydrogen phosphate stock solutions in different proportions.

[0045] NH3·H2O-NH4Cl buffer solution was prepared by mixing 0.1 mol / L ammonia water and ammonium chloride stock solution in different proportions.

[0046] The heavy metal ion solution was prepared by dissolving the corresponding nitrate in water, and the element quantitative analysis was performed using an inductively coupled plasma mass spectrometer (ICP-MS). Take the lead ion solution as an example: 16.56g of lead nitrate was dissolved in 400mL of water and the volume was fixed in a 500mL volumetric flask to prepare a 0.1mol / L lead ion solution. The actual lead ion concentration was then quantitatively determined by ICP-MS. Take 1mL of the 0.1mol / L lead ion solution and dilute it by 10 3 times to get 1×10 -4 mol / L lead ion solution.

[0047] 3) Electrochemical test method:

[0048] Square wave anodic stripping voltammetry (SWASV) was used to detect Pb(II). Specifically, three windows were set to complete the electrochemical test, and the three windows corresponded to the enrichment window (window one), the redox window (window two) and the desorption window (window three).

[0049] Among them: Window 1 is the time-current program, with an enrichment voltage of -1.1 V and a time of 180 s.

[0050] Window 2 is the square wave anodic stripping voltammetry (SWASV) window, with a voltage setting range of -1.0-0V, a frequency of 25Hz, and an amplitude of 25mV.

[0051] Window three is the time-current window, with a desorption voltage of 1.0 V and a time of 90 s.

[0052] The current limit of the three windows is 1×10 -4 A.

[0053] 4) Condition optimization:

[0054] By controlling variables, the type of buffer solution, pH value, enrichment voltage and enrichment time were optimized to obtain the optimal experimental conditions.

[0055] First, three Bi@S-doped g-C3N4 / GCE working electrodes prepared in step 1) were taken and immersed in 10 mL of HAc-NaAc, PBS, and NH3·H2O-NH4Cl buffer solutions with a pH of 5, respectively.

[0056] The same concentration of 0.1 mmol / L Pb(II) solution prepared in step 2) was added to the above three solutions respectively. Under the same enrichment time and enrichment voltage, the response current values ​​were compared, and the optimal buffer solution was HAc-NaAc.

[0057] In this buffer solution, five identical Bi@S-doped g-C3N4 / GCEs were immersed in HAc-NaAc buffer solutions of pH=3, 4, 5, 6, and 7, respectively. Under the same voltage and time, the optimal pH was pH=5.

[0058] Next, in a HAc-NaAc buffer solution at pH = 5, the voltage and enrichment time were optimized in turn, with the optimal enrichment time being 180 s and the enrichment voltage being -1.1 V.

[0059] The optimal experimental conditions were obtained as follows: pH = 5, HAc-NaAc buffer solution, enrichment time 180s, and enrichment voltage -1.1V.

[0060] 5) Electrochemical test:

[0061] The electrochemical test of Pb(II) was carried out under the above-mentioned optimal experimental conditions (pH=5, HAc-NaAc buffer solution, enrichment time 180s, enrichment voltage -1.1V).

[0062] The first thing to do is to conduct a baseline test: immerse the three-electrode system in a glass bottle containing 10ml of HAc-NaAc buffer solution (the glass bottle contains a magnet), turn on stirring, and start window one for enrichment. Turn off stirring when there are 6-8s of enrichment time left until window one is completed, and start window two for the redox process (no stirring is required for this process). After window two is finished, turn on stirring and start window three for desorption. The SWASV response curve obtained in window two can be recorded as baseline 1. Repeat the enrichment-redox-desorption process to obtain different baselines in turn until the last baseline coincides with the previous baseline, which means that the baseline is stable, and then heavy metal ion testing can be performed.

[0063] Heavy metal ion test: Add 10μL of 0.1mmol / L Pb(II) solution to 10ml of HAc-NaAc buffer solution to obtain the corresponding SWASV response curve, and record the response current as 0.1mmol / L Pb(II) solution. After window three desorption is completed, add 10μL of 0.1mmol / L Pb(II) solution, and record the response current as 0.2mmol / L Pb(II) solution. After repeated addition, complete the response current value recording of 0.1-0.8mmol / L Pb(II) solution in turn. And obtain the response current and concentration equation through linear fitting.

[0064] like Figure 2 As shown in pH = 5, HAc-NaAc buffer solution; its linear equation is y = 57.45x + 0.56, and its slope represents the electrochemical sensitivity, which is as high as 57.45 μA / μM.

[0065] The theoretical detection limit LOD was calculated according to the calculation formula LOD = 3SD / S, where SD is the standard deviation of the response current value of 0.1-0.8mmol / L Pb(II) solution, and S is the sensitivity. The calculated theoretical detection limit (LOD) was 0.04μM, which is lower than 0.048μM in the National Drinking Water Standard (GB5749-2022).

[0066] Embodiment 2:

[0067] S1. Place urea in a muffle furnace and set the temperature program to two stages: the first stage is to heat up to 350°C at a heating rate of 5°C / min and keep it for 2 hours; the second stage is to heat up to 600°C at a heating rate of 5°C / min and keep it for 1 hour, then anneal to obtain a g-C3N4 substrate material.

[0068] S2. Add 16 mg of the g-C3N4 substrate material prepared above, 5 mg of Bi(NO3)3·5H2O, and 100 mg of thioacetamide to 20 mL of deionized water (the molar ratio of Bi to S is 1:133), and stir magnetically at 40°C for 3 hours to obtain a uniform mixed solution.

[0069] S3, evaporating the mixed solution to dryness at 30° C. and 0.1 kp using a rotary evaporator to obtain a powdered solid, and grinding the powdered solid to obtain a ground material;

[0070] S4. Place the ground material in a muffle furnace and perform two-stage calcination as in step S1, then cool to room temperature, grind, and sieve to obtain Bi@S-doped g-C3N4 nanomaterials.

[0071] Embodiment 3:

[0072] S1. Place urea in a muffle furnace and set the temperature program to two stages: the first stage is to heat up to 450°C at a heating rate of 5°C / min and keep it for 1.5 hours; the second stage is to heat up to 550°C at a heating rate of 5°C / min and keep it for 1.5 hours, then anneal to obtain a g-C3N4 substrate material.

[0073] S2. Add 16 mg of the g-C3N4 substrate material prepared above, 10 mg of Bi(NO3)3·5H2O, and 100 mg of thioacetamide to 20 mL of deionized water (the molar ratio of Bi to S is 2:133), and stir magnetically at 70°C for 1 hour to obtain a uniform mixed solution.

[0074] S3, evaporating the mixed solution at 60° C. and 0.5 kp using a rotary evaporator to obtain a powdered solid, and grinding the powdered solid to obtain a ground material;

[0075] S4. Place the ground material in a muffle furnace and perform two-stage calcination as in step S1, then cool to room temperature, grind, and sieve to obtain Bi@S-doped g-C3N4 nanomaterials.

[0076] Embodiment 4:

[0077] The same as Example 1, the only difference is that in step S2, the amount of Bi(NO3)3·5H2O added is 20 mg.

[0078] Embodiment 5:

[0079] The same as Example 1, the only difference is that in step S2, thioacetamide is replaced by L-cysteine, and the added amount thereof is 161 mg.

[0080] Comparative Example 1:

[0081] The same as Example 1, the only difference is that in step S2, the amount of thioacetamide added is 0 mg. Comparative Example 2:

[0082] The same as Example 1, the only difference is that in step S2, the amount of Bi(NO3)3·5H2O added is 0 mg. Comparative Example 3:

[0083] Same as Example 5, except that in step S2, the amount of L-cysteine ​​added is 0 mg.

[0084] As in Test Example 1, the materials prepared in Examples 1-5 and Comparative Examples 1-3 were made into working electrodes, and electrochemical tests of 0.6 μM Pb (II) were performed under the same experimental conditions (pH=5, HAc-NaAc buffer solution, enrichment time 180 s, enrichment voltage -1.1 V). The test results are shown in the following table:

[0085]

[0086] like Figure 3 As shown in the figure, when other substances are the same, different amounts of Bi(NO3)3·5H2O are added, and the detection response to 0.6μM Pb(Ⅱ) is obtained. Figure 3 It can be seen that with the increase of Bi(NO3)3·5H2O addition amount, the current value increases, but reaches the maximum value when the addition amount is 15 mg, and then decreases.

[0087] It can be seen from the above table that when Bi(NO3)3·5H2O is not added, Pb(Ⅱ) cannot be detected; when sulfur-containing non-metallic materials are not added, the detection current of heavy metal Pb ions at the same concentration is significantly reduced, reflecting a decrease in detection sensitivity.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing Bi@S doped g-C3N4 nanomaterials, characterized in that: The following steps are involved: S1, calcining urea to obtain a g-C3N4 substrate material; S2, adding g-C3N4 substrate material, Bi(NO3)3·5H2O and sulfur-containing non-metallic material into deionized water, heating and stirring to obtain a uniform mixed solution; The sulfur-containing non-metallic material is thioacetamide or L-cysteine; S3, heating and evaporating the mixed liquid to obtain a precursor; and then grinding it uniformly; S4. The ground precursor is calcined, cooled, and then ground again to obtain Bi@S-doped g-C3N4 nanomaterials.

2. The preparation method according to claim 1, characterized in that: The calcination in steps S1 and S4 refers to two-stage heating, wherein the first stage is heating the temperature to 350-450°C and keeping it for 1-2 hours; the second stage is continuing to heat to 500-600°C and keeping it for 1-2 hours.

3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the g-C3N4 base material and Bi(NO3)3·5H2O in the mixed solution is 16:(5-20), and the molar ratio of Bi and S elements is (1-4):

133.

4. The preparation method according to claim 1, characterized in that: The heating and stirring in step S2 is carried out at 40-70° C. with magnetic stirring for 1-3 hours.

5. The preparation method according to claim 1, characterized in that: In step S3, the mixed solution is evaporated to dryness by heating at 30-60° C. and 0.1-0.9 kp using a rotary evaporator.

6. A Bi@S doped g-C3N4 nanomaterial prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the Bi@S doped g-C3N4 nanomaterial as claimed in claim 6 in detecting heavy metal ions in water.

8. The use according to claim 7, characterized in that: The heavy metal ion is Pb(II), and its detection limit is 0.04 μM and the detection sensitivity is 57.45 μA / μM.

9. The use according to claim 7, characterized in that: The detection of heavy metal ions in water is carried out using a three-electrode detection system, which includes a working electrode, and the working electrode is a GCE electrode with a Bi@S-doped g-C3N4 nanomaterial coated on the surface.

10. The use according to claim 9, characterized in that: The detection conditions of the three-electrode detection system are: pH=5, HAc-NaAc buffer solution, enrichment time of 180s, and enrichment voltage of -1.1V.